Desenvolvimento de um aplicativo computacional para dimensionamento técnico e econômico de biodigestores tipo tubular - Alves , Anelisiane Maria (2017)
Technological and economic development occurred through the extraction of the environment and industrialization in a globalized model of society. This model is now fully dependent on sources of energy to continue to function. However, due to the environmental politicization and the problematization of the use of fossil sources, the search for an alternative energy model has been the subject of academic research and public policies for some years. The present work focuses on the development of a computational program that will provide the user, often unaware of the research in development, with the access and the necessary guidance for the implantation of a tubular rural biodigester. The application was developed in Java language, where the technical and economical sizing methodology used takes into account data such as the type and number of animals and the user's monthly electricity consumption. After the program processes the calculation routine, the user is presented the results in 3 different screens, one containing a generic image with the nomenclature adopted for the estimated dimensions, a screen with technical information of the design and a final screen with information of economic projection. This work is expected to disseminate and democratize alternative research and technologies through the use of digital technology.